Tolerância religiosa e direitos da religião católica no constitucionalismo espanhol e português : primeira metade do século xix - Cristina Nogueira da Silva (Mélanges de la Casa de Velázquez, 2014)
This article seeks to comprehend how the principle of religious toleration was received in the Spanish and Portuguese Constitutions of the first half of the 19th century. However, it is far from exhausting the subject—which is important enough to warrant taking this research further, in particular with information about how constitutional decisions influenced legislation and the resolution of conflicts in the jurisprudence of the time and impacted on the life of religious minorities in both countries. Here we seek above all to establish a comparison based on the constitutions, on the legislation and also on the work of historians published on the subject in either country.